Effect of Microplastic Exposures to The Male Gonad Histology of Catfish (Clarias gariepinus) - Anggita Noer Laily; Mohamad Fadjar; Yuni Kilawati (Department of Aquaculture, 2023)
Aquaculture activities cannot be separated from obstacles that can lead to failure of aquaculture, including the presence of microplastics. Microplastic polystyrene (styrofoam) is a type of plastic that is commonly found in aquatic organisms (35%). Microplastics in fish can cause hormonal disturbances and high vacuolation in gonads which can cause apoptosis in gonadal cells. This study aimed to determine the effect of microplastics exposure on catfish (Clarias gariepinus) feed on the gonadal histology of male catfish. The research design used an experimental method with a Completely Randomized Design (CRD) which was divided into four treatments and three replications, namely 3% of the feed rate with treatments A (5% microplastics), B (10% microplastics), C (15% microplastics), and K (0% microplastics). Microplastic exposure treatment was given to fish by mixing it with commercial feed for 30 days. The results showed that microplastic exposure had a significant effect on the 15th and 30th days of the study on the Gonad Maturity Level (GML) and Gonado Somatic Index (GSI) of male catfish (C. gariepinus) in treatments A, B and C compared to controls (K). Treatment C (Microplastics 15%) had the lowest GML and GSI values, while treatment K (Microplastics 0%) had the highest GML and GSI values. Treatments A, B, and C experienced changes and delays in the development of gonadal cell structure, while control (K) developed well. This is presumably because the nutritional needs of control fish (K) were more fulfilled than treatments A, B and C exposed to microplastics.